2017
DOI: 10.1117/1.jei.26.1.011026
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of flat natural and cultural heritage objects by a Compton scattering modality

Abstract: Characterization and interpretation of flat ancient material objects, such as those found in archaeology, paleoenvironments, paleontology, and cultural heritage, have remained a challenging task to perform by means of conventional x-ray tomography methods due to their anisotropic morphology and flattened geometry. To overcome the limitations of the mentioned methodologies for such samples, an imaging modality based on Compton scattering is proposed in this work. Classical x-ray tomography treats Compton scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is also possible to consider interior sources, for instance via the insertion of radiotracers like in SPECT. Then considering collimated detectors, it is possible to model the scattered flux through conical radon transforms, see for instance [33,36]. However, in this work, we consider only systems with external sources.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to consider interior sources, for instance via the insertion of radiotracers like in SPECT. Then considering collimated detectors, it is possible to model the scattered flux through conical radon transforms, see for instance [33,36]. However, in this work, we consider only systems with external sources.…”
Section: Introductionmentioning
confidence: 99%
“…This class of Radon transform in R 3 , in the so-called compounded . From top to bottom: original phantom, direct inversion, inversion after normalizing values following z-axis, inversion after removing voxels located at edges of single reconstructions of dimensions 4×4×32 voxels, reprinted from [39] form, supports a remarkable imaging process known as Compton scatter SPECT imaging which can provide directly the three dimensional image of the interior of an object by a standard gamma camera functioning in a fixed spatial position. The absence of rotational motion characteristic of standard SPECT imaging represents a major advantage resulting from the exploitation of scattered gamma rays for imaging purpose.…”
Section: Resultsmentioning
confidence: 99%
“…They may be fed into the inversion formula (see [15] to reconstruct the object electron density. As we shall see, the second procedure with back scattering turns out to be relevant for cultural heritage research imaging [38,39], (see section 6).…”
Section: Three-dimensional Compton Scattered Radiation Imaging and Vamentioning
confidence: 99%
“…As a follow-up, each spectrum in the dataset can be expressed (i.e., modeled) as a linear combination of the calculated latent variables, returning chemically relevant weight matrices. A more detailed review of methods to perform dimensionality reduction to obtain chemical maps can be found in (Guerrero Prado et al 2017).…”
Section: Integrating Computational Methodologies In the Processing Of...mentioning
confidence: 99%